Specific Features of Vascular Endothelium in Patients with Severe Forms of Inflammatory Bowel Diseases - O. V. Khlynova; E. A. Stepina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. In this work, we set out to assess the specific features of vascular endothelium in patients suffering from severe (pan-ulcerative) and complicated forms of ulcerative colitis (UC) and Crohn’s disease (CD).Materials and methods. The research sample consisted in 65 patients with UC (n = 45) and CD (n = 20), who were either in the acute phase or had been diagnosed with such conditions for the first time. For assessing endothelial dysfunction (ED), we used such markers as levels of vascular endothelial growth factor (VEGF) in the blood serum and the number of plasma desquamated endotheliocytes (DEC).Results. The indicators of vascular endothelial dysfunction are shown to be significantly higher in patients with severe, pan-ulcerative forms of inflammatory bowel diseases (IBD). A statistically significant relationship has been established between ED indicators and the severity and localisation of the pathological process, the extra-intestinal manifestations and complications of the disease. A dependence of the endothelial dysfunction indicators on the UC endoscopic activity has been determined. A positive correlation between the levels of VEGF and DEC and the markers of systemic inflammation (ESR, CRP and fibrinogen) has been revealed.Conclusion. It is determined that, in IBD patients, endothelium dysfunction is manifested in an increase in the VEGF and DEC levels. The indicators of endothelial dysfunction are shown to be directly correlated with the serum markers of systemic inflammation. Therefore, VEGF and DEC values can be used not only as criteria for assessing the intensity of IBD, but also as predictors of a complicated disease course.